Development and Evaluation of formulations for Enhanced Antimicrobial & Antiphotoaging Activities of Anacardic Acid - Anjum, Md Meraj (IIT BHU VARANASI, 2020)
Abstract is available in content.
Keywords: Antiphotoaging Activities of Anacardic Acid; Enhanced Antimicrobial Activities of Anacardic Acid